The Attitude Towards the Subject of History in General Education in Vietnam through a Survey from the Student's Perspective - Nhung, Dao Thi Tuyet (VNU Journal of Science: Education Research, 2024)
Factors include teaching methods, influence from parents, influence from friends, careers related to the field of history, negative feelings about the subject and personal characteristics, all affect learning attitudes towards history subjects. Furthermore, through the use of open-ended questions, the research delved into the causes and reasons behind the lack of interest in the subject of history such as quite long knowledge, many timelines, and difficult to remember; problems from the teacher; the issue belongs to the individual preferences; or the nature of the subject including boring, long, dry, lacking visual images in teaching. An important proposal stemming from the research results is the need to innovate approaches to history subjects by using gamification. The research has shown that integrating gamification into the history learning process can lead to significant improvements in efficiency. In particular, using role-playing games based on historical stories is considered a high-performance solution to enhance interaction and efficiency in the learning process.